Ensuring the Industrial Safety of Hazardous and Potentially Hazardous Production Facilities through the Use of an Original Complex Method for Assessing the State of Metal in Technical Diagnosis - Stanislavovich, Snarsky Andrey; Ivanovich, Panteleenko Fedor (European Journal of Life Safety and Stability (2660-9630), 2022)
The issues of ensuring industrial safety during the operation of various production facilities through the use of an effective integrated methodology for assessing the metal of critical metal (steel) structures in their technical diagnostics are considered: pressure vessels; technological and main pipelines; crane structures. The expediency of using three main non-destructive methods of control is experimentally substantiated: magnetic (by coercive force); metallographic (using the principles of field metallography and portable microscopes) and durometric (connecting the parameters of the imprint of a pyramidal indenter when determining Vickers hardness with the mechanical properties of the material).